What Is This Love That Loves Us?: Terrence Malick's To the Wonder as a Phenomenology of Love - Hamilton, Julie M. (Religions, 2016)
Terrence Malick's To the Wonder (2013) considers the relationship of Divine Love with the individual soul, and its corresponding relationships to the other as neighbor. In this article, I analyze the congruency of Malick's form and content by correlating the relationship of his dynamic, existential filmmaking style with the film's phenomenologically constructed plotline. Jean-Luc Marion's phenomenology of givenness and Søren Kierkegaard's Works of Love contribute to my analysis, aiding our understanding of love's sheer gratuity and sacrificial labor, amid inevitable idolatry and despondency, in To the Wonder's intersecting narratives. While Marion helps us comprehend the affective qualities of saturated phenomena in the film's formal dimensions, Kierkegaard elucidates the film's many iterations of love. Malick aesthetically demonstrates the reciprocity of love and the experience of wonder as contingent operations, making To the Wonder a cinematic phenomenology of the fractured yet indissoluble dimensions of love.